Greater Endothelial Apoptosis and Oxidative Stress in Patients with Peripheral Artery Disease. (20th May 2014) - Gardner, Andrew W.; Parker, Donald E.; Montgomery, Polly S.; Sosnowska, Danuta; Casanegra, Ana I.; Ungvari, Zoltan; Csiszar, Anna; Sonntag, William E.
Abstract : We compared apoptosis, cellular oxidative stress, and inflammation of cultured endothelial cells treated with sera from 156 subjects with peripheral artery disease (PAD) and 16 healthy control subjects. Furthermore, we compared circulating inflammatory, antioxidant capacity, and vascular biomarkers between the two groups. The PAD group had a 164% higher value for endothelial cell apoptosis (P < 0.001 ) and a 62% higher value for endothelial cellular reactive oxygen species production (P < 0.001 ) than the control group. Furthermore, the PAD group had lower systemic antioxidant capacity measured by hydroxyl radical antioxidant capacity activity (P < 0.001 ), higher inflammatory and vascular measures of high-sensitivity C-reactive protein (P < 0.001 ), interleukin-8 (P < 0.001 ), serum amyloid A (P < 0.001 ), vascular cell adhesion molecule-1 (P < 0.001 ), adiponectin (P < 0.001 ), apolipoprotein B (P = 0.013 ), apolipoprotein CIII (P = 0.035 ), lower vascular endothelial growth factor-A (P < 0.001 ), and hepatocyte growth factor (P < 0.001 ) than the control group. Subjects with PAD have greater endothelial apoptosis and oxidative stress than control subjects with low burden of comorbid conditions and cardiovascular risk factors. Furthermore, subjects with PAD have lower systemic antioxidant capacity and angiogenic measures and higher circulating inflammatory parameters.